ナンキョク ノ チメイ - 原田, 美道; ハラダ, ヨシミチ; HARADA, Yoshimichi (国立極地研究所, 1964)
P(論文) Japanese geographic nomenclature in Antarctica was decided by Japanese Promotive Headquarters of Antarctic Research Expedition (J.P.H.A.R.E.) in 1961, based on the policy of United States Advisory Committee on Antarctic Names. Until 1963 total 98 place names were decided by Antarctic Names Committee of Japan, Ministry of Education, and authorized by J.P.H.A.R.E. Those names are classified by First class, Second class and Third class generally. The provisional gazetteer will be published in the near future, in which all official names and their descriptions are contained. Place name lists are shown in Appendices 1, 2 and 3, and new names are located in Figs. 1, 2 and 3 respectively. Exact geographical positions are shown in the topographic maps which are being compiled by Geographical Survey Institute. Errata | http://id.nii.ac.jp/1291/00007312/ departmental bulletin paper